Neurologic Complications of Celiac Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Patients with celiac disease (CD) [n=l 11] and controls (n=211) were questioned regarding neurologic disorders, their charts were reviewed, and they received neurologic evaluations, including brain imaging or EEG if indicated, in a study of neurologic complications of CD at Carmel Medical Center, Technion-Israel Institute of Technology, Haifa, Israel.